2021
DOI: 10.5812/jkums.107638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Problem-solving Skills Training on the Anxiety and Sleep Quality of Patients After Coronary Artery Bypass Graft Surgery

Abstract: Background: Cardiovascular diseases are the leading cause of mortality worldwide, and sleep disturbance and anxiety play a key role in the prognosis of these patients. Objectives: The present study aimed to evaluate the effects of problem-solving skills training (PSST) on the anxiety and sleep disturbance of cardiac patients. Methods: This quasi-experimental study was carried out in three stages before, after, and during a two-month follow-up after eight PSST sessions (one hour each). Sample population include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For example, Thoma et al showed that teaching social problem-solving skills was effective in treating mental disorders (30). Also, the results of the studies of Omidi et al showed the effect of teaching SPSST on anxiety, sleep quality, and depression in heart patients (31,32). Another study showed the effect of short-term training of…”
Section: Discussionmentioning
confidence: 99%
“…For example, Thoma et al showed that teaching social problem-solving skills was effective in treating mental disorders (30). Also, the results of the studies of Omidi et al showed the effect of teaching SPSST on anxiety, sleep quality, and depression in heart patients (31,32). Another study showed the effect of short-term training of…”
Section: Discussionmentioning
confidence: 99%
“…Polat and Simsek showed that even a short period of skill training is effective in reducing depression and increasing the quality of life of heart inpatients (28). Omidi, et al showed that this skill positively affects cardiac patients' anxiety and sleep quality after CABG (29). In addition, Vollman et al showed that heart patients who used problem-solving skills are less likely to have anxiety and depression symptoms than other patients and can control these factors well (30).…”
Section: Discussionmentioning
confidence: 99%